Researching Ageing Methodological Challenges and their Empirical Background - Łuszczyńska, Maria (Routledge Advances in Research Methods, 2020)
This book explores the diversity of methodological approaches to researching ageing, considering which methodological paradigm best captures the phenomenon. Interdisciplinary in scope, it brings together research from scholars from Austria, Canada, France, Hong Kong, Israel, Poland, UK and USA to uncover the conditions under which qualitative and quantitative approaches to research on ageing can best be reconciled and rendered complementary. Presenting international reflection on methods for studying old age from a variety of research backgrounds, Researching Ageing showcases the latest research in the field and will appeal to scholars across the social sciences, including sociology, demography, psychology, economics and geography, with interests in gerontology, ageing and later life.